The Nutritional Status Profile of Physical Education Teachers - Priyono, Bambang; Rozi, Fatkhur; Joseph, Jacklyn Anak (Faculty of Sport and Health Sciences, 2023)
The purpose of this study was to describe the quality of the physical education teacher's nutritional status and its theoretical impact. The research data is qualitative in nature and is generated from filling out open questionnaires to informants. 124 informants voluntarily filled out the questionnaire and came from various regions in Indonesia, for this reason, informant data was protected. Data analysis was carried out in a qualitative descriptive manner by collecting data, reducing, presenting, verifying, and concluding. The results showed that 1 person was in the underweight category, 71 people were in the healthy weight (normal) category, 27 people were in the overweight category, and 25 people were in the obese category. The conclusions of this study indicate that only 59% of teachers have a healthy weight nutritional status and the rest are in an unhealthy (not ideal) position which will have an impact on their fitness and health levels, as well as showing the performance of personal and professional competencies that has not been maximized.